Prevascularized spongy-like hydrogels maintain their angiogenic potential after prolonged hypothermic storage - Sara Freitas-Ribeiro; Helena Moreira; Lucília P. da Silva; Jennifer Noro; Belém Sampaio-Marques; Paula Ludovico; Mariana Jarnalo; Ricardo Horta; Alexandra P. Marques; Rui L. Reis; Rogério P. Pirraco (Bioactive Materials, 2024)
The chronic shortage of organs and tissues for transplantation represents a dramatic burden on healthcare systems worldwide. Tissue engineering offers a potential solution to address these shortages, but several challenges remain, with prevascularization being a critical factor for in vivo survival and integration of tissue engineering products. Concurrently, a different challenge hindering the clinical implementation of such products, regards their efficient preservation from the fabrication site to the bedside. Hypothermia has emerged as a potential solution for this issue due to its milder effects on biologic systems in comparison with other cold preservation methodologies. Its impact on prevascularization, however, has not been well studied. In this work, 3D prevascularized constructs were fabricated using adipose-derived stromal vascular fraction cells and preserved at 4 °C using Hypothermosol or basal culture media (α-MEM). Hypothermosol efficiently preserved the structural and cellular integrity of prevascular networks as compared to constructs before preservation. In contrast, the use of α-MEM led to a clear reduction in prevascular structures, with concurrent induction of high levels of apoptosis and autophagy at the cellular level. In vivo evaluation using a chorioallantoic membrane model demonstrated that, in opposition to α-MEM, Hypothermosol preservation retained the angiogenic potential of constructs before preservation by recruiting a similar number of blood vessels from the host and presenting similar integration with host tissue. These results emphasize the need of studying the impact of preservation techniques on key properties of tissue engineering constructs such as prevascularization, in order to validate and streamline their clinical application.